Turning proteins into hydrophobic floatable materials with multiple potential applications - Hu, Teh-Min; Lin, Chien-Yu; Chou, Hung-Chang; Wu, Meng-Ju (Journal of colloid and interface science, 2019)
[Display omitted] Protein hydrogels are water-rich structure of cross-linked protein networks. The preparation of dry gels is conceptually simple. However, reports on innovative use of dry protein hydrogels are scarce, possibly because water removal would diminish intended properties. Here, an oil-like thiol-organosilane is proposed as a protein hydrogel-promoting agent that mediates the formation of hydrophobic composite gel networks with promising properties upon drying. 3-Mercaptopropyltrimethoxylsilane (MPTMS) was used to transform aqueous albumin solutions into hydrogels. The gelation conditions were systematically investigated and optimized by varying various parameters, including temperature, pH, and the concentrations of MPTMS, albumin, and phosphate. The hydrogels were freeze-dried to obtain dry gel monoliths. The morphology of gel structure was evaluated using FE-SEM. The following properties of the dry monoliths were further evaluated: water uptake, floatability, drug loading and release, water contact angles, bulk densities, and oil adsorption. Mechanistic investigation included FTIR and fluorescence quenching determinations, and the study of emulsion properties. An unprecedented protein-organosilane composite hydrogel was synthesized in a one-step reaction, at neutral pH and ambient conditions. Freeze-dried gel monoliths exhibited excellent hydrophobicity and floatability (immediate floating and lasting for >7 days on water). The proposed material may find novel applications in floating drug delivery and environmental clean-up of oil spills.